Recent advances in the use of temporary silicon tethers in metal-mediated reactions. - Bracegirdle, S; Anderson, E (2010)
This tutorial review describes the use of temporary silicon tethers in metal-mediated organic reactions, a strategy which although well-established in traditional organic synthesis is still a blossoming field in the organometallic arena. The benefits of silicon-tethering are manifold: the reactivity, selectivity, and efficiency of organometallic processes can all be dramatically enhanced, often with unique regio- and stereochemical outcomes compared to the analogous intermolecular transformations. In addition, the residual silicon functionality can undergo a wide range of chemistry subsequent to the tethered reaction, creating further synthetic opportunities.